The Derivation Of A Design Matrix For A Foot-mounted Inertial Pedestrian Navigation Using Invariant Observer Approach - A. A. Rahman; N. S. M. Khairi; K. Abdulrahim (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Journal of Engineering and Technology (JET), Volume 15 Issue 1 Page (125-139)